2015
DOI: 10.1016/j.cogpsych.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

How do people learn from negative evidence? Non-monotonic generalizations and sampling assumptions in inductive reasoning

Abstract: A robust finding in category-based induction tasks is for positive observations to raise the willingness to generalize to other categories while negative observations lower the willingness to generalize. This pattern is referred to as monotonic generalization. Across three experiments we find systematic non-monotonicity effects, in which negative observations raise the willingness to generalize. Experiments 1 and 2 show that this effect emerges in hierarchically structured domains when a negative observation f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 43 publications
8
53
0
Order By: Relevance
“…This work complements recent studies that highlight the impact of social and pragmatic constraints on the sampling process in property inference (Hayes et al, under review;Ransom et al, 2016;Shafto et al, 2014;Voorspoels et al 2015). In everyday inference the samples of evidence that we observe are often likely to be subject to both types of constraints; frame-like limitations that systematically exclude certain types of data as well as data selected with a particular social goal (e.g., to teach or to mislead).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…This work complements recent studies that highlight the impact of social and pragmatic constraints on the sampling process in property inference (Hayes et al, under review;Ransom et al, 2016;Shafto et al, 2014;Voorspoels et al 2015). In everyday inference the samples of evidence that we observe are often likely to be subject to both types of constraints; frame-like limitations that systematically exclude certain types of data as well as data selected with a particular social goal (e.g., to teach or to mislead).…”
Section: Discussionsupporting
confidence: 72%
“…A growing body of evidence suggests that people's inductive inferences are guided by their understanding of the sampling processthe method by which observations were generated or selected (e.g., Navarro, Dry, & Lee, 2012;Shafto, Goodman, & Griffiths, 2014;Tenenbaum & Griffiths, 2001;Voorspoels, Navarro, Perfors, Ransom, & Storms, 2015;Xu & Tenenbaum, 2007). Much of the previous work in this area has examined sampling processes as a form of social cognition: people reason differently when they believe data were selected by a helpful teacher than when data are selected randomly, or when deception is involved.…”
Section: Data Censoring Sampling and Bayesian Reasoningmentioning
confidence: 99%
See 1 more Smart Citation
“…A promising new approach views relevance theory in the context of people's beliefs about how and why premises have been sampled from the set of possible observations. These sampling assumptions are instantiated in a formal Bayesian model of belief revision (Ransom et al, ; Shafto, Goodman, & Griffiths, ; Voorspoels, Navarro, Perfors, Ransom, & Storms, ). A key insight is that reasoners often assume that the premises presented in an inductive argument have been selected intentionally by a helpful agent to highlight a salient property of the premises.…”
Section: Theoretical Explanations Of Knowledge Effectsmentioning
confidence: 99%
“…It has also been shown to predict novel phenomena involving negative evidence. For example, Voorspoels et al () showed that adding negative evidence to a premise set can increase belief in conclusions about how far a property can be generalized. For example, those who learned that “Mozart's music elicits alpha waves” but that “falling rocks do note elicit alpha waves” were more likely to conclude that “Metallica's music elicits alpha waves,” than those who were only given positive evidence.…”
Section: Theoretical Explanations Of Knowledge Effectsmentioning
confidence: 99%